Symptoms of non-gonococcal urethritis in heterosexual men: a case control study. Issue 2 (30th March 2005) - Iser, P; Read, TR H; Tabrizi, S; Bradshaw, C; Lee, D; Horvarth, L; Garland, S; Denham, I; Fairley, C K
Abstract : Objective: To determine microbial and behavioural factors contributing to non-gonococcal urethral symptoms in men. Methods: Case-control study of heterosexual men with non-gonococcal urethral symptoms (cases) and without urethral symptoms (controls) attending Melbourne Sexual Health Centre, Australia. Sexual behaviour and condom use were measured by questionnaire. First stream urine was tested for potential pathogens: Chlamydia trachomatis (ligase chain reaction), Mycoplasma genitalium (polymerase chain reaction, PCR), Ureaplasma urealyticum (culture and PCR), and Streptococcus spp, Gardnerella vaginalis, and Haemophilus species (culture). Urethral smears from cases were examined for polymorphonuclear leucocytes. Results: 80 cases and 79 controls were recruited over 4 months in 2002–3. 49 cases (61%) had urethritis by microscopic criteria, 17 (21%) had Chlamydia trachomatis (adjusted odds ratio (OR) 27 (95% confidence interval (CI): 3.4 to 222)), five (6%) had Mycoplasma genitalium (OR 6.1 (95% CI: 0.6 to 61)), and 11 (14%) had Gardnerella vaginalis (OR 9.0 (95% CI: 1.6 to 52)). Other organisms were not significantly associated with urethral symptoms. The presence of urethritis on urethral smear did not predict the presence of Chlamydia trachomatis (OR 1.7 (95% CI: 0.5 to 5.4)). Urethral symptoms were significantly associated with unprotected vaginal sex with more than one casual partner (OR 9.3 (95% CI: 1.3 to 65)) and unprotected anal sex with a regular partner in the past month (OR 3.5 (95% CI: 1.0 to 13)). Conclusion: Gardnerella vaginalis and unprotected anal sex may cause symptoms of non-gonococcal urethritis. Microscopy of the urethral smear to diagnose urethritis in this population does not help to identify which men with urethral symptoms require treatment for chlamydia.